2003
DOI: 10.1175/bams-84-6-785
|View full text |Cite
|
Sign up to set email alerts
|

The Advanced Very High Resolution Radiometer Pathfinder Atmosphere (PATMOS) Climate Dataset: A Resource for Climate Research

Abstract: A recent reprocessing of AVHRR data results in a 20-yr global climate dataset providing information on the earth's radiation budget T he National Oceanic and Atmospheric Administration/National Environmental Satellite, Data, and Information Service (NOAA/NESDIS) has generated a consistent, calibrated, dataset of atmospheric products derived from nearly 20 yr of observations from Advanced Very High Resolution Radiometers (AVHRR) on board NOAA polar-orbiting satellites. This began as a partnership with the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 16 publications
(8 reference statements)
4
56
0
Order By: Relevance
“…Various active and passive satellite cloud climatologies exist; for example, the active Cloud Profiling Radar (CPR) (Stephens et al, 2008) and Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) sensors are able to provide height-resolved information on cloud properties (Winker et al, 2007), however, coverage is limited to the subsatellite track and the time-series are short. Of the passive satellite instruments the most widely known are the High resolution Infrared Sounder (HIRS, Wylie and Menzel, 1999), Moderate Resolution Imaging Spectroradiometer (MODIS, Platnick et al, 2003), Advanced Very High Resolution Radiometer (AVHRR, Jacobowitz et al, 2003;Heidinger and Pavolonis, 2009) and Multi-angle imaging SpectroRadiometer (MISR, Moroney et al, 2002) datasets. The passive sensors cannot represent the complex vertical structure, but have much better global coverage and longer time series than active instruments.…”
Section: A Poulsen Et Al: Cloud Retrieval Algorithmmentioning
confidence: 99%
“…Various active and passive satellite cloud climatologies exist; for example, the active Cloud Profiling Radar (CPR) (Stephens et al, 2008) and Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) sensors are able to provide height-resolved information on cloud properties (Winker et al, 2007), however, coverage is limited to the subsatellite track and the time-series are short. Of the passive satellite instruments the most widely known are the High resolution Infrared Sounder (HIRS, Wylie and Menzel, 1999), Moderate Resolution Imaging Spectroradiometer (MODIS, Platnick et al, 2003), Advanced Very High Resolution Radiometer (AVHRR, Jacobowitz et al, 2003;Heidinger and Pavolonis, 2009) and Multi-angle imaging SpectroRadiometer (MISR, Moroney et al, 2002) datasets. The passive sensors cannot represent the complex vertical structure, but have much better global coverage and longer time series than active instruments.…”
Section: A Poulsen Et Al: Cloud Retrieval Algorithmmentioning
confidence: 99%
“…Observations from narrowband scanning radiometers (AVHRR and HIRS) have been used (Wielicki et al, 2002a, data supplement http://www.sciencemag.org/cgi/ content/full/295/5556/841/DC1) to derive broadband longwave radiative fluxes: AVHRR OLR fluxes showed a decrease of 2 Wm −2 /decade in the tropical region, for the period 1985-2000, while HIRS OLR data showed an increase of about 1 Wm −2 /decade for the same period. In the recent reprocessing of AVHRR data, which resulted in the PATMOS climate dataset, Jacobowitz et al (2003) examined the time-series of the OLR at TOA, in the tropics (20 • N-20 • S), for the period from September 1981 through to December 1999. They found that the OLR decreased by a little less than 2 Wm −2 for the period from 1985 to 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Passive meteorological satellite imagers provide important information for investigating cloud properties (Stephens and Kummerow, 2007), and for quantifying their influence on solar (Deneke et al, 2005) and thermal (Schmetz et al, 1990) radiation. Several projects generate data records of cloud properties, including the International Satellite Cloud Climatology Project (ISCCP, Rossow and Schiffer, 1991), the Pathfinder Atmospheres project (PAT-MOS, Jacobowitz et al, 2003), the MODIS project (Platnick et al, 2003), and the Satellite Application Facility on Climate Monitoring (CM-SAF, Schulz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by Heidinger and Stephens (2001), unresolved spatial heterogeneity can cause errors in retrieved cloud properties large enough to render them useless. To partly overcome this problem, Klüser et al (2008) utilized the high-resolution broadband visible channel (HRV) with a sampling resolution of 1×1 km 2 at nadir to study the lifecycle of shallow convective clouds.…”
Section: Introductionmentioning
confidence: 99%